Canine alopecia X-Like disorder - Crawford, Megan; Lundberg, Annette; Neto, Rachel (Brazilian Journal of Veterinary Pathology, 2024)
Clinical History: A 6-year-old spayed female Samoyed dog was presented to the Dermatology Service at Auburn University Veterinary Teaching Hospital (AUVTH) for a 6-month history of non-pruritic alopecia on the hips and back, with the skin turning black in those areas (Figures 1 and 2). The animal had a prior history of hypothyroidism (controlled at the time of evaluation) and a urinary tract infection. The dog was on levothyroxine, Interceptor plus, Nexgard, fish oil, and Royal Canin Veterinary Diet Adult Urinary SO Dry Dog Food. There was no travel history outside the Southern United States. This animal was cohoused with another healthy dog. Bloodwork was unremarkable and testing for Cushing’s disease was negative. Skin scrapes, cytology, and dermatophyte and bacterial cultures were negative.